The use of heritage & culture preservation in textile museum advertising campaign / Nor Lely Zuraidah Mohd Azaman - Mohd Azaman, Nor Lely Zuraidah (Faculty of Art and Design, 2013)
Throughout Asia textiles are one of the most powerful and exciting art form, and in Southeast Asian in particular, the spiritual and ritual importance that textiles play in ceremonies of state and religion is reflected in their great mystery and splendor. Southeast Asian textiles are outstanding works art, formed by a rich variety of techniques. The examples often of elaborate and complex design, display superb levels of technical skill in weaving, dyeing, embroidery and applique. The National Textile Museum showcases the origins, development and techniques of local textiles and the role they have had in the rich and diverse heritage of Malaysia. It is housed in a beautiful old heritage building on Merdeka Square in the heart of Kuala Lumpur's main tourist area. The Mughal style building was designed by AB Hubback (who designed so many of the city's most famous landmarks) and was completed in 1905 as headquarters for the Federated Malay States Railways. In 1917 the building was subsequently handed over to the Selangor Public Works department and over the following decades it served as premises for the Selangor Water Department, the Central Bank, Agricultural Bank, Malaysian Craft and the High Court before being refurbished as a museum. The National Textile Museum opened to the public in 2010. It was gazette as a historical building in 1983 and is divided into four galleries arranged over two floors. The first gallery is the is Pohon Budi Gallery. This gallery covers the tools, materials and techniques of textile making over the ages. Displays include calendaring and gilding, gold thread embroidery, embroidered shawls, head cloths and tapestries, Iban ceremonial cloth, songket equipment, Royal Pahang weaving, beaded shoes, tie-dye, canting, printing and block and freehand techniques. The second is Pelangi Gallery. This gallery exhibits different types of batik over the years, collections from the Chinese, Baba and Nyonya communities which are rich in the use of gold thread and beading, together with examples of ethnic Sarawak and Sabah a textile motifs. The third galleries are named Teluk Berantai Gallery. Moving upstairs, this gallery concentrates on the Teluk Berantai (interlocking bays), a harmonious motif made up of individual flower designs stitched together into geometric patterns, which is predominant in Malay textile designs. Exhibits include Malay textiles, Indian textiles, gold thread embroidery and examples of the woven silk, cotton, velvet and pineapple fabric garments which make up traditional Malay costumes. Last is Ratna Sari Gallery. This gallery showcases diamond, gold, silver, copper and other jewelry items and personal adornments worn by different ethnic communities in Malaysia. Collections include tobacco boxes, chastity belts, belts, buckles, headdresses, hair pins, waist accessories, pendants, brooches, beaded shoes, bracelets, anklets, hats, earrings, rings, weapons, necklaces and mannequins wearing attire from Iban, Murut, Indian, MahMeri, Malay and Baba Nyonya communities. Investigate, preserve, document and display a collection of textile heritage the country to promote awareness and understanding of the values, ethics and aesthetics in the production, use, application, acculturation and development textile. A diversity of materials includes bark, plant fibers, cotton, silk, beads, shells, gold and silver, and among a profusion of patterns and motifs we find human figures, abstract, geometric shapes, ships, arabesques, calligraphy, flowers, recognizable animals and imaginary monsters.